AB0970 Improvement of the Long-Term Outcome in Greek Adult Patients with Juvenile Idiopathic Arthritis in the 21St Century. (9th June 2015) - Dimopoulou, D.; Trachana, M.; Pratsidou-Gertsi, P.; Sidiropoulos, P.; Theodoridou, A.; Kanakoudi, F.; Garyfallos, A.
Abstract : Background: During the last decade there is evidence of a rising improvement regarding the long-term outcome of patients with Juvenile Idiopathic Arthritis (JIA). Objectives: To compare long-term outcome between patients with disease onset before and after 2000. Methods: Patients (pts) ≥18 years with an established JIA, a disease onset ≥5 years and no history of >6 months care from external rheumatologists, were enrolled in the study. Clinical, laboratory and radiographic examination were performed at the last follow-up visit, 17.2 years post-diagnosis. The outcome variables were: radiographic damage assessed by the total modified Sharp/van der Heijde Score (TmSvdHS), articular and extra-articular damage by Juvenile Arthritis Damage Index (JADI-A and JADI-E) and physical ability by the Health Assessment Questionnaire-Disability Index (HAQ-DI). In the multivariate analysis, possible explanatory variables were characteristics present at onset and active disease duration within 5 years of onset. Results: A total of 102 (72 F) pts were enrolled. The age at disease onset (mean ± SD) was 7.7±4 yrs, the interval from onset to last visit 17.2±6.7 yrs and the pts' current age 25±5.9 yrs. 28 patients were diagnosed after 2000 (Group 1) and 74 patients before 2000 (Group 2). The 2 Groups didn't differ in demographic and clinical characteristics, as gender, type of disease onset and ACPA positivity. At the last follow-up visit, Group 1 had better TmSvdHS, better JADI-A and better JADI-E score as compared to Group 2 (p<0.001, p<0.001, p=0.003, respectively). In contrast, HAQ-DI score did not differ between the 2 Groups (p=0.55) but disease duration within 5 yrs of onset was longer in Group 2 (p=0.02). Prognostic factors for joint damage were disease duration [B (95%CI) 2.114 (0.206, 4.022), p=0.03], cumulative % time spent in a state of active disease [B (95%CI) 0.007 (0.004, 0.011), p<0.001] and cumulative time spent in a state of clinical remission off medication over the entire disease course [B (95%CI) -0.667 (-1.048, -0.286), p=0.001]. Conclusions: Pts diagnosed after 2000, had a better long term outcome as compared to those before 2000. Despite the difference in disease duration, active disease duration within 5 years of onset proved to be a critical prognostic factor, probably reflecting the availability of biologics nowadays and the treat-to-target strategies. References: Minden K. Adult outcomes of patients with juvenile idiopathic arthritis. Horm Res 2009; 72:20-25. Disclosure of Interest: None declared